ASSOCIATION BETWEEN REPRODUCTIVE HEALTH KNOWLEDGE AND EXTERNAL GENITAL HYGIENE BEHAVIOR AMONG ADOLESCENT GIRLS IN SENIOR HIGH SCHOOL - Yuni Yastutik, Iryani; Ratna Aminati, Fifi; Kristiana, Ike (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2026)
Background: Adolescent reproductive health literacy plays a critical role in preventing infections and promoting healthy hygiene behaviors. However, many adolescent girls still lack adequate knowledge and appropriate external genital hygiene practices. Objectives: This study aimed to analyze the association between reproductive health knowledge and external genital hygiene behavior among adolescent girls. Methods: A cross-sectional study was conducted in 2023 among all female students at a senior high school using total sampling. Data were collected using a validated questionnaire whose content validity index (CVI) was assessed by three experts and reliability tested using Cronbach’s alpha (knowledge α = 0.82; behavior α = 0.79). Data were analyzed using Chi-square tests with a 95% confidence level. Ethical approval was obtained from the institutional ethics committee. Results: Most respondents demonstrated good knowledge (X%) and good hygiene behavior (X%). Chi-square analysis showed a statistically significant association between reproductive health knowledge and external genital hygiene behavior (p < 0.05). Conclusion: Higher reproductive health knowledge is significantly associated with better external genital hygiene behavior among adolescent girls. Strengthening school-based reproductive health education and improving hygiene facilities is recommended.